Characterisation of Mycenaean and matt-painted pottery from Alani, ancient upper Macedonia, Greece - Iordanidis, A.; Garcia-Guinea, J.; Karamitrou-Mentessidi, G. (Bulletin of the Geological Society of Greece, 2007)
Several analytical methods were applied for the study of ancient pottery from Aiani, ancient upper Macedonia, northern Greece. Mycenaean and matt-painted pottery sherds, dated form Late Bronze age, were analysed with the help of X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF) and Environmental Scanning Electron Microscopy, coupled with Energy Dispersive X-ray system (ESEM-EDX). Morphological, chemical and mineralogical characteristics of both types of ancient pottery indicated a rather local provenance, thus strengthening the hypothesis of the co-existence of Mycenaean and Dorian pottery workshops in the region, during Late Bronze period